IMPLEMENTASI PROGRAM KEEP IT SHINY AND SUSTAINABLE (KiSS) DALAM MENGANTISIPASI KERUSAKAN LINGKUNGAN (STUDI KASUS MUGELLO CIRCUIT TAHUN 2013-2016) - Indri Utari; Irwan Iskandar (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2017)
This research describes the implementation of Keep It Shiny and Sustainable (KiSS) programme in order to anticipation of environment damage study case in Mugello Circuit in 2013 – 2016. The first edition of the KiSS was held at the Mugello in 2013 through the Motorcycle Grand Prix (MotoGP) events, promoted by The Fédération Internationale de Motocyclisme (FIM) with the objective of involving the public through environmentally and socially sustainable initiatives. Mugello Circuit, located in an extremely important natural landscape in Tuscany, Italy and since 2011 the circuit has been on the cutting edge in terms of environmental sustainability.This facility obtained the environmental management certification International Organisation for Standarization (ISO) 14001: 2004, dan Environmental Management and Audit Scheme (EMAS) dan Occupational Health and Safety Advisory Services (OHSAS) 18001: 20072007 as to health and safety. In Europe and in Italy, Environmental Management and Audit Scheme (EMAS), is regarded as the reference scheme for environmental certifications. Italy has endorsed EU Regulation 1836/1993 - later updated by Regulation 761/2001 - through the 1996 Ministerial Decree which introduces EMAS.The research method is a qualitative-descriptive with the combination of library research and field research technic. For the library research, writter collects the data from journals, books, official reports, mass media and websites to analyze this research. For the field research, writter collects the data from interview through email. The perspective applied in this research is Green Thought persepective with theories and concept applied such as International Organization theory, Sustainable Development concept and Green Politics theory.Key words: implementation, KiSS, FIM, MotoGP, Mugello Circuit, EMAS